Nutrient Acquisition by Plants An Ecological Perspective - BassiriRad, Hormoz (Ecological Studies, Analysis and Synthesis,, 2005)
Adaptation and evolution of terrestrial plants depend, to a large extent, on their ability to acquire nutrients. This is a modern and integrative treatment of the mechanisms controlling plant nutrient uptake and how plants respond to changes in the environment. The following key topics are covered: soil nutrient bioavailability; root responses to variations in nutrient supply; nitrogen fixation; regulation of nutrient uptake by internal plant demand; root characteristics; kinetics of nutrient uptake; root architecture; life span; mycorrhizae; responses to climate change. This integrated view helps us to understand the mechanisms that govern present-day plant communities and is indispensable in models designed to predict the response of plants to a changing climate.